2015
DOI: 10.1007/s00392-015-0922-4
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte–platelet aggregates and CD11b expression as markers for thrombogenicity in atrial fibrillation

Abstract: The content of MPAs and the CD11b expression on monocytes and granulocytes are increased in AF-patients with proven thrombus formation. They seem to be appropriate biomarkers for stratification of thromboembolic risk in patients with AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 53 publications
0
17
0
2
Order By: Relevance
“…Moreover, inflammatory mediators favour to a pro-thrombotic state [16, 17], which may account for the increased risk of thromboembolism and cardiovascular mortality also in this setting. Hence, the relationship between inflammation and cardiovascular events in patients with AHREs deserves further research.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inflammatory mediators favour to a pro-thrombotic state [16, 17], which may account for the increased risk of thromboembolism and cardiovascular mortality also in this setting. Hence, the relationship between inflammation and cardiovascular events in patients with AHREs deserves further research.…”
Section: Discussionmentioning
confidence: 99%
“…Edoxaban inhibits platelet aggregation in vitro to a higher degree compared with fondaparinux 25. To further evaluate the effect of apixaban on platelet activity in AF, investigations of other platelet markers are needed 26. In contrast to sCD40L, vWF antigen levels were elevated in a proportion of patients independent of VKA status before randomisation.…”
Section: Discussionmentioning
confidence: 99%
“…To ascertain whether these statins regulated systemic inflammation in inflammatory arthritis, we assessed the levels of platelet–leukocyte aggregates in peripheral blood from arthritic mice, given the relationship of these heterotypic aggregates and cellular activation with CVD (26, 27). Using flow cytometry, we found that atorvastatin regulated the expression of CD11b on both nonclassic and classic monocytes as well as platelet–monocyte aggregates as measured by a decrease in CD62P ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Leukocytes, including monocytes, are implicated in the propagation of various aspects of CVD (26, 27). Studies investigating the role of different monocyte subsets in atherosclerosis, for example, found elevated classic and nonclassic monocytes in atherosclerotic plaques (33).…”
Section: Discussionmentioning
confidence: 99%